1990
DOI: 10.1002/cjce.5450680514
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of oleic acid with oxygen in the presence of benzaldehyde using heterogenized homogeneous co‐type ion‐exchange membrane as catalyst

Abstract: The epoxidation of oleic acid with oxygen in the presence of benzaldehyde to produce epoxidized oleic acid using a Co‐type ion‐exchange membrane as catalyst was carried out. No leakage of cobalt ion was found during the experimental runs. The epoxidized oleic acid was formed by a series of free radical reactions. Experimental results show that at 70% conversion of oleic acid, 60% of the total theoretical epoxidized oleic acid was obtained, illustrating the high selectivity (86%). The rate‐determining steps wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Formation of the ternary complex can be depicted as follows: where A = oleic acid, E = free enzyme, B = hydrogen peroxide, AE = enzyme-oleic acid complex, ABE = ternary complex of the enzyme + oleic acid + hydrogen peroxide, EQ = enzymeperoleic acid complex, P = water, and Q = peroleic acid. The rate or velocity (v) equation obtained with the above mechanism is as follows: [2] where V max = maximum velocity, K iA = dissociation constant for enzyme-oleic acid complex, K mA = Michaelis constant for oleic acid, K mB = Michaelis constant for hydrogen peroxide, and K 1 i = inhibition constant due to hydrogen peroxide. Based on crystallographic and molecular modeling studies of Lipase B from C. antarctica, it is postulated that the active site pocket can be partitioned into two sides, an acyl side and an alcohol side, where the corresponding parts of the substrate will be located during catalysis (16).…”
Section: Resultsmentioning
confidence: 99%
“…Formation of the ternary complex can be depicted as follows: where A = oleic acid, E = free enzyme, B = hydrogen peroxide, AE = enzyme-oleic acid complex, ABE = ternary complex of the enzyme + oleic acid + hydrogen peroxide, EQ = enzymeperoleic acid complex, P = water, and Q = peroleic acid. The rate or velocity (v) equation obtained with the above mechanism is as follows: [2] where V max = maximum velocity, K iA = dissociation constant for enzyme-oleic acid complex, K mA = Michaelis constant for oleic acid, K mB = Michaelis constant for hydrogen peroxide, and K 1 i = inhibition constant due to hydrogen peroxide. Based on crystallographic and molecular modeling studies of Lipase B from C. antarctica, it is postulated that the active site pocket can be partitioned into two sides, an acyl side and an alcohol side, where the corresponding parts of the substrate will be located during catalysis (16).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would be interesting to replace the processes based on peracids by a more desirable catalytic one. [8][9][10][11][12] Recently, it has been shown that the incorporation of Ti into the framework of zeolites produce oxidation catalysts with unique shape-selective properties. 13 Large-pore Ti-b zeolite 14 and the mesoporous material Ti-MCM-41, 15 when properly prepared, are active for the selective oxidation of bulky substrates that can not diffuse inside the Ti-silicalite channels.…”
mentioning
confidence: 99%
“…This reaction has been applied to the epoxidation of unsaturated fatty acid derivatives. Surprisingly, the epoxidation was mainly carried out using benzaldehyde . Despite this, both high yield and selectivity toward epoxide were achieved.…”
Section: Introductionmentioning
confidence: 99%